ALIRAN PERENIALISME DAN IMPLEMENTASINYA DALAM PENDIDIKAN ISLAM - Eko Nursalim; Khojir Khojir (Cross-border, 2021)
This article was written with the aim of analyzing and interpreting the concept of perennial, the history of development and perennial figures and their implementation in Islamic education. The research method in this article is a qualitative research method. The type is library research, and the data analysis is descriptive analysis. The result is the concept of perennial implied a message about the existence of immortality in values and norms. Perennialism is not a new school in philosophy. Perennialism in education is motivated by the philosophical thoughts of Plato, Aristotle, Thomas Aquinas in his day. As for the figures of perennials, namely Frithjof Schuon and Seyyed Hossein Nasr, the two figures above are characters who tend to be perennial. The implementation in the world of Islamic education can be found in the goals of Islamic education, the role of educators and students, Islamic education curriculum, methods and evaluation of learning